2013
DOI: 10.1039/c3lc00055a
|View full text |Cite
|
Sign up to set email alerts
|

Radiochemistry on chip: towards dose-on-demand synthesis of PET radiopharmaceuticals

Abstract: We have developed an integrated microfluidic platform for producing 2-[(18)F]-fluoro-2-deoxy-D-glucose ((18)F-FDG) in continuous flow from a single bolus of radioactive isotope solution, with constant product yields achieved throughout the operation that were comparable to those reported for commercially available vessel-based synthesisers (40-80%). The system would allow researchers to obtain radiopharmaceuticals in a dose-on-demand setting within a few minutes. The flexible architecture of the platform, base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
48
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 60 publications
(48 citation statements)
references
References 17 publications
0
48
0
Order By: Relevance
“…Available literature has demonstrated that this approach might be feasible for producing a stream of purified FDG out of a continuously running MCS apparatus. This prototype actually reported the integration of the whole production process in a very compact flow system that generated a continuous stream of product, starting from a continuous feed of radiofluorination complex and chemicals (Arima et al 2013) (Fig. 8.21).…”
Section: Microfluidics In Radiochemistry Integrated Systemsmentioning
confidence: 99%
“…Available literature has demonstrated that this approach might be feasible for producing a stream of purified FDG out of a continuously running MCS apparatus. This prototype actually reported the integration of the whole production process in a very compact flow system that generated a continuous stream of product, starting from a continuous feed of radiofluorination complex and chemicals (Arima et al 2013) (Fig. 8.21).…”
Section: Microfluidics In Radiochemistry Integrated Systemsmentioning
confidence: 99%
“…The first batch microfluidic synthesis of [ 18 F]FDG was demonstrated in a polydimethylsiloxane (PDMS) chip with 40 nL reaction volume [14]. Microvalves [19], Copyright © 2013 Elsevier, Inc.) (g) EWOD chip with reaction volume ranging from 2 to 17 μL were used to close the reactor during reaction steps, and the permeability of the PDMS enabled escape of vapor for solvent exchange processes.…”
Section: Platforms For Microliter Volume Synthesismentioning
confidence: 99%
“…This system should implement the reduction to the minimum possible of the amounts of radioactivity and chemicals needed in the preparation, added to an overall simplification of the production process. Such conceptual process can be defined as "Dose On Demand" (DOD) [3,4,5]: the operation of producing a radiopharmaceutical in the shortest time possible, using the minimum amount of chemicals and radioactivity strictly needed for the production of the single (or few) imaging dose (s) required.…”
Section: Dod Featuresmentioning
confidence: 99%